MATHEMATICAL MODELING FLOW IN PIPELINES WITH LEAKS IN THE ENVIRONMENT - Олійник, Андрій Петрович; Мороз, Аліса Андріївна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The mathematical model that allows determining the leak rate of the product is transported in soil that surrounds technological or main pipeline. Based on modeling viscous fluid flow system using Navies-Stokes equations and its numerical realization of the model was developed from current leakage, the model and its numerical realization conducted a broad class of future payments.